Pemanfaatan Limbah Stirofoam dan Karet Ban Sebagai Bahan Isolator Panas - Sania Bulan Zurahma; Wiji Utami (Fakultas Sains dan Teknologi, UIN Sulthan Thaha Saifuddin Jambi, 2025)
Rapid industrial development has caused an increase in the volume of waste such as styrofoam and rubber tires that are difficult to degrade naturally in nature. Utilization of waste as a thermal insulator is one of the best solutions and can overcome environmental problems. This material component has low thermal conductivity properties because of its ability to inhibit heat. The study aims to determine the effectiveness of Styrofoam and rubber tires at each additional thickness of the thermal insulator in retaining heat. This study uses an experimental method by observing the comparison of different material thickness variations, namely 0, 1, 3, 5 cm and measuring the temperature every 5 minute interval, for half an hour. The results of each measurement of the addition of styrofoam and rubber tires at a thickness of 5 cm produced the smallest heat transfer. The results of the average temperature comparison at a thickness of 5 cm of styrofoam were 69.28 ℃ while rubber tires were 67 ℃. This also shows the ability of styrofoam to retain heat better than rubber tires. The data from this study can be used as a reference in the management of styrofoam and rubber tire waste. This research innovation can contribute to the problem of waste that is difficult to degrade naturally.